A review of religious education in Malaysia and Thailand / Nor Tasik Misbahrudin, Abd Halim Mohd Noor and Chanchai Rittiruam - Misbahrudin, Nor Tasik; Mohd Noor, Abd Halim; Rittiruam, Chanchai (Universiti Teknologi MARA, 2021)
Education is one of the important agendas in the development of a country. Every country has a unique educational system to offer its citizens. Mostly there are few types and levels of education offered by the government of a country. In Malaysia, the Ministry of Education and the Ministry of Higher Education are responsible for overseeing education matters. Besides mainstream education, Malaysia is also popular with religious education. Since Malaysia is an Islamic country, the majority of religious education in the country is centered on Islam, and Tahfiz education is the most widely practiced. Currently, this education has received a huge interest among parents and children itself. In contrast to Thailand, Thai Buddhist temples have surpassed all other learning institutions as the primary source of religious instruction for the vast majority of the populace. The education is focused on monastic, which is divided into four categories. Hence, this article will review the religious education practices in Malaysia as well as Thailand. This study used library research to gather all information of religious education from both countries. It is found that both religious education in these countries has developed in recent years, becoming more systematic and gaining in popularity.